Re-inventing researcher identity: when the individual interacts with the contextual power dynamics - Mertkan, Sefika; Bayrakli, Hatice (Routledge Journals, Taylor & Francis Ltd, 2018)
This article is about being and becoming a qualitative researcher in Turkey, a context with a distinctive quantitative tradition shaped by the post-positivist paradigm where qualitative research has not yet reached the mature stage it enjoys elsewhere. Exploring the challenges of swimming against the tide unattended and keeping going, it argues learning to do research is more about crafting an identity than it is about learning a set of tools and techniques. Rather, it is a process largely influenced by the context in which the researcher's identity is shaped, one that is characterized by power dynamics and identity negotiations. These issues are largely neglected in the literature.
Keywords: Doctoral education; qualitative research; researcher identity; higher education